FACTORS OF READINESS OF FUTURE PSYCHOLOGISTS TO WORK WITH SINGLE-PARENT FAMILIES (Psychology Travelogs, 2024)
The article presents a theoretical analysis of the factors that can influence the readiness of future psychologists to work with single-parent families. In this context, modern researchers express an opinion on the issue of improving the quality of education and providing the state with competent highly qualified psychologists whose activities will be aimed at preserving and restoring the mental well-being of families. After all, the professional training of future psychologists is determined by public demand, which includes tasks for quality interaction with single-parent families.A clear outline of many practical and theoretical problems, as well as the creation of relevant new legislation, supplemented by programmes in higher education institutions for psychological support of members of single-parent families, namely those families formed as a result of military aggression by Russia, necessitates the identification of socio-psychological factors that affect the readiness of future psychologists to work with single-parent families.It has been determined that the process of formation of psychology students' readiness to work with single-parent families depends on a number of factors of objective and subjective nature. Among various factors, special attention is drawn to the following: organization of the process of educational and practical training in higher educational institutions, selection of the educational program components which allow providing a system of competencies necessary for psychological assistance of single-parent families, the student's natural psychotherapeutic inclinations and abilities, internal motivation, and the student's desire to engage in family counseling and therapy.
Keywords: future psychologists; work; readiness; factors; single-parent families